Comparative Efficacies of Antimicrobial Catheter Lock Solutions for Fungal Biofilm Eradication in an in Vitro Model of Catheter-Related Fungemia - Joel Rosenblatt; Ruth A. Reitzel; Nylev Vargas-Cruz; Anne-Marie Chaftari; Ray Hachem; Issam I. Raad (Journal of Fungi, 2017)
Fungal catheter-related bloodstream infections (CRBSIs)—primarily due to Candida species—account for over 12% of all CRBSIs, and have been progressively increasing in prevalence. They present significant health and economic burdens, and high mortality rates. Antimicrobial catheter lock solutions are an important prophylactic option for preventing fungal CRBSIs. In this study, we compared the effectiveness of two FDA-approved catheter lock solutions (heparin and saline) and three experimental antimicrobial catheter lock solutions—30% citrate, taurolidine-citrate-heparin (TCH), and nitroglycerin-citrate-ethanol (NiCE)—in an in vitro model of catheters colonized by fungi. The fungi tested were five different strains of Candida clinical isolates from cancer patients who contracted CRBSIs. Time-to-biofilm-eradication was assessed in the model with 15, 30, and 60 min exposures to the lock solutions. Only the NiCE lock solution was able to fully eradicate all fungal biofilms within 60 min. Neither 30% citrate nor TCH was able to fully eradicate any of the Candida biofilms in this time frame. The NiCE lock solution was significantly superior to TCH in eradicating biofilms of five different Candida species (p = 0.002 for all).